RIDING AS A SPORT OF TERAPEUTIC NATURE NARRATIVE STUDY - Burzawa, Katarzyna Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The healing effects of horse riding have been known for a long time. These qualities were already recognized in ancient times - Hippocrates believed that riding a horse stimulates the functioning of the body, while Socrates noticed its impact on the exercise of the body and senses. In turn, Avicenna considered horse riding to be an excellent exercise for the body. In the sixteenth century, doctors confirmed the beneficial effects of horse riding, considering it useful for health. In 1750, Francisco Fuller mentioned horse riding in the first study of sports medicine, noticing its impact on the state of mind and human body (Bednarczyk 2015). The horse played a huge role in human life, and the nature of this relationship has changed over the years. The subject of the article focuses on the equestrian sport, which therapeutic effect takes place through the constant dialogue between the rider and the horse. This relationship is manifested in a special relationship of man and animal, which has an emotional character. The phenomenon of this interaction was presented in the Amazon narrative, which through riding and communing with these animals, has found a new dimension of life. The research was embedded in qualitative orientation, which allowed to understand a fragment of the narrator's reality and her experience of everyday life.